(untitled) (Journal of the College of Basic Education, 2025)
This study aims to explore the impact of the M.U.R.D.E.R strategy on the scientific thinking of fifth-grade female students in the science subject. To achieve this goal, the researchers formulated the following null hypothesis: There is no statistically significant difference at the 0.05 level between the mean scores of the experimental group students, who were taught using the M.U.R.D.E.R strategy, and the control group students, who were taught the same material using the traditional method, in the scientific thinking test. A quasi-experimental design with partial control was adopted, consisting of an experimental group and a control group. A multiple-choice test was used to measure scientific thinking among fifth-grade students. The sample was randomly selected from Imam Ali Primary School for Girls, comprising 70 students divided equally into two randomly assigned sections: the experimental group (32 students) received instruction based on the M.U.R.D.E.R strategy, while the control group (33 students) was taught using conventional methods. To achieve the study’s objectives, a scientific thinking test was developed, consisting of 30 items in its final version. The validity of the test was confirmed, and its reliability was measured using the Kuder-Richardson Formula 20 (KR-20), yielding a reliability coefficient of 0.87, indicating a high level of internal consistency and making the test suitable for research purposes. Upon completion of the experiment and data analysis using appropriate statistical tools, the results revealed that the experimental group students significantly outperformed their counterparts in the control group in terms of scientific thinking. Based on these findings, the researchers proposed a set of recommendations and suggestions, which are presented in the fourth chapter.